Governing the surgical count through communication interactions: implications for patient safety. Issue 5 (30th October 2006) - Riley, R; Manias, E; Polglase, A
Abstract : Background: Intermittently, the incidence of retained surgical items after surgery is reported in the healthcare literature, usually in the form of case studies. It is commonly recognised that poor communication practices influence surgical outcomes. Aim: To explore the power relationships in the communication between nurses and surgeons that affect the conduct of the surgical count. Methods: A qualitative, ethnographic study was undertaken. Data were collected in three operating room departments in metropolitan Melbourne, Australia. 11 operating room nurses who worked as anaesthetic, instrument and circulating nurses were individually observed during their interactions with surgeons, anaesthetists, other nurses and patients. Data were generated through 230 h of participant observation, 11 individual and 4 group interviews, and the keeping of a diary by the first author. A deconstructive analysis was undertaken. Results: Results are discussed in terms of the discursive practices in which clinicians engaged to govern and control the surgical count. The three major issues presented in this paper are judging, coping with normalisation and establishing priorities. Conclusions: The findings highlight the power relationships between members of the surgical team and the complexity of striking a balance between organisational policy and professional judgement. Increasing professional accountability may help to deal with the issues of normalisation, whereas greater attention needs to be paid to issues of time management. More sophisticated technological solutions need to be considered to support manual counting techniques.